2003
DOI: 10.3168/jds.s0022-0302(03)73611-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Treating Alfalfa with Lactobacillus buchneri 40788 on Silage Fermentation, Aerobic Stability, and Nutritive Value for Lactating Dairy Cows

Abstract: Lactobacillus buchneri 40788 and enzymes (beta-glucanase, alpha-amylase, xylanase, and galactomannase) were applied to chopped alfalfa (39% DM) to study their effects on the fermentation and nutritive value of the silage. Alfalfa was treated with nothing, or L. buchneri 40788, for a final application rate of 1 x 10(5), 5 x 10(5), or 1 x 10(6) cfu/g of fresh forage and ensiled in laboratory silos for 2, 4, 8, and 56 d. Treatment with L. buchneri 40788 had few effects on the end products of fermentation through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
111
4
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(140 citation statements)
references
References 16 publications
16
111
4
9
Order By: Relevance
“…Bulls fed TMR containing sugarcane silage inoculated with L. buchneri had higher DMI (P = 0.006; Table 4). Several studies have shown that when cattle or sheep are fed silages treated with L. buchneri, DMI is not affected (Driehuis et al, 1999;Taylor et al, 2002;Ranjit et al, 2002;Kung et al, 2003). However, in the present study, the inoculants were effective in mitigating NDF accumulation caused by sugar oxidation during the ensiling process and improved the DMI.…”
Section: Resultscontrasting
confidence: 38%
“…Bulls fed TMR containing sugarcane silage inoculated with L. buchneri had higher DMI (P = 0.006; Table 4). Several studies have shown that when cattle or sheep are fed silages treated with L. buchneri, DMI is not affected (Driehuis et al, 1999;Taylor et al, 2002;Ranjit et al, 2002;Kung et al, 2003). However, in the present study, the inoculants were effective in mitigating NDF accumulation caused by sugar oxidation during the ensiling process and improved the DMI.…”
Section: Resultscontrasting
confidence: 38%
“…Data on microbial population and quality of sugar cane silage is still scarce, while data on the microbiology of other fodders silages such as sorghum, wheat, maize, alfalfa, and grasses in general has been reported by several researchers (8,13,15,18,25,29). In corn and sorghum silages stored for 90 days, yeasts counting were 3.86 and 4.18 Log CFU g -1 of silage, respectively, and lactic acid counting was 8.35 and 7.92 Log CFU g -1 of silage, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Yeasts play an important role on the silage quality. Some species might develop in anaerobic conditions, are capable of surviving at low pH values (3.5), and are not inhibited by lactic acid (13). These yeasts convert fodder soluble sugars into ethanol, CO 2 and water, which results in high dry matter loss and low quality forage (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Imediatamente após a abertura dos silos (45 dias após ensilagem), todo o conteúdo de silagem foi retirado, homogeneizado e acondicionados em baldes plásticos, mantidos em temperatura ambiente, para a avaliação da estabilidade aeróbica. A análise da estabilidade aeróbica foi realizada com base na diferença entre a temperatura da silagem e a temperatura do bulbo seco (TBS) do ambiente, na qual foi analisado o tempo (horas) necessárias para a temperatura do silo se igualar a TBS, e se elevar em 2, 5 e 10ºC acima da TBS, de acordo com a metodologia sugerida por Kung et al (2003). Após 24 horas de exposição aeróbica foram realizadas as análises de pH, posteriormente em intervalos de 24 horas até às 296 horas, de acordo com as metodologias preconizadas por Silva & Queiroz (2002).…”
Section: Introductionunclassified